2000
DOI: 10.1074/jbc.m004700200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Promoter of Human Leukocyte-specific Transcript 1

Abstract: The gene for the human leukocyte-specific transcript 1 (LST1) encodes a small protein that modulates immune responses and cellular morphogenesis. The LST1 transcripts are expressed at high levels in dendritic cells. Because of the complex splicing pattern, use of alternative 5-untranslated exons, and a biologically interesting pattern of expression of LST1 mRNA, we studied the human LST1 gene promoter and regulatory elements. We identified an additional upstream 5-untranslated exon in U937 monocytic cells. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In the present study we focussed on the uORF of exon 1B (uORF4, Figure 1A) for several reasons. First, exon 1B is the most widely used exon 1 variant in LST1 : roughly two thirds of all transcripts include the exon 1B sequence [8]. Second, the stop codon of uORF4 is located only 66 bp upstream of the main ORF and its last codon encodes proline (Figure 1C), a feature that has been shown to delay termination and therefore inhibit binding of other ribosomes to downstream ORFs in close proximity [20], [21].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study we focussed on the uORF of exon 1B (uORF4, Figure 1A) for several reasons. First, exon 1B is the most widely used exon 1 variant in LST1 : roughly two thirds of all transcripts include the exon 1B sequence [8]. Second, the stop codon of uORF4 is located only 66 bp upstream of the main ORF and its last codon encodes proline (Figure 1C), a feature that has been shown to delay termination and therefore inhibit binding of other ribosomes to downstream ORFs in close proximity [20], [21].…”
Section: Resultsmentioning
confidence: 99%
“…The LST1 gene lacks typical TATA promoter sequences and transcription factor binding sites. The region downstream of exon 1B up to exon 1C contains potential binding sites for transcription factors and was identified as the sequence with highest promoter activity in reporter assays [8]. The authors also identified sequences just upstream of exon 1B with protein binding sites but the respective nuclear factors could not be identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations